Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How to solve $$\lim_{n\rightarrow \infty}\frac{(\log n)^p}{n}$$

share|improve this question

6 Answers 6

up vote 2 down vote accepted

Note that $\displaystyle\frac{(\log n)^p}{n}=p^p\cdot\left(\frac{\log k}k\right)^p$, where $k=n^{1/p}\to\infty$ when $n\to\infty$.

share|improve this answer

Replace $n$ by $2^n$ and take the limit to $\infty$.

share|improve this answer
    
That, assuming the sequence in $n$ converges. –  Pedro Tamaroff Jun 28 '12 at 18:29

Let $A=\lim_{n\to\infty} \frac{(\log n)^p}{n}$.Taking $log$ both sides gives $\log A=\lim_{n\to\infty} (p\log \log n -\log n)=\lim_{\log n\to\infty} (p\log \log n -\log n) $.Take $y=1/\log n\implies \log A=\lim_{y\to0^+} (-p\log y -1/y) \implies \log A=\lim_{y\to0^+} \frac{-py\log y -1}{y}$.This limit surely goes to $-\infty$ and hence $\log A=-\infty\implies A=0$.Thus the limit is $0$.

share|improve this answer

Let $\displaystyle a(n) = \frac{\log^p n}{n}$. Notice that $\displaystyle \frac{a(n^2)}{a(n)} = \frac{2^p}{n}$.

share|improve this answer
    
hi. My first thought was to replace $n$ by $2^n$. Then you're done. –  Chris's sis Jun 28 '12 at 18:12
    
@Chris: There are many ways to go here! Another choice would be $n\to e^n$. –  user26872 Jun 28 '12 at 18:18
    
well, that way is already used by Marvis. :-) –  Chris's sis Jun 28 '12 at 18:20
    
Oops. Sometimes I am not a careful reader! –  user26872 Jun 28 '12 at 18:24
    
hehe. Neither do i all the time. –  Chris's sis Jun 28 '12 at 18:26

Apply $\,[p]+1\,$ times L'Hospital's rule to$\,\displaystyle{f(x):=\frac{\log^px}{x}}$: $$\lim_{x\to\infty}\frac{\log^px}{x}\stackrel{L'H}=\lim_{x\to\infty}p\frac{\log^{p-1}(x)}{x}\stackrel{L'H}=\lim_{x\to\infty}p(p-1)\frac{\log^{p-2}(x)}{x}\stackrel{L'H}=...\stackrel{L'H}=$$ $$\stackrel{L'H}=\lim_{x\to\infty}p(p-1)(p-2)...(p-[p])\frac{\log^{p-[p]-1}(x)}{x}=0$$ since $\,p-[p]-1<0\,$

share|improve this answer
    

Let $n = e^t$ and let $r = \lceil p \rceil+1$. Then $e^t > \dfrac{t^{r}}{r!}$, since $\displaystyle e^t = \sum_{k=0}^{\infty} \dfrac{t^k}{k!}$. Hence, $$0 \leq \lim_{n \to \infty} \dfrac{\log^p n}{n} = \lim_{t \to \infty} \dfrac{t^p}{e^t} < \lim_{t \to \infty} \dfrac{r!}{t^{r-p}} \leq \lim_{t \to \infty}\dfrac{r!}{t} = 0$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.